Comparisons of heart rate and energy expenditure during exergaming in college-age adults - Oh, Y.; Johnson, L. E.; Olson, J. R.; Shea, K. R.; Braun, S. (International Journal of Computer Science in Sport, 2017)
The purpose of this study was twofold: 1) to discover the differences in degree of energy expenditure (EE) during Just Dance 2015 using Xbox 360 Kinect, Wii-U, PS3 Move, and Control YouTube video; and 2) to uncover whether or not exergaming could elicit moderate to vigorous levels of intensity (= 40% Heart Rate Reserve (HRR)) based on heart rate average (HRavg) measurements. Twenty-five healthy college-aged students participated in this study. Data collection was comprised of baseline testing, a 30 second familiarization period with each gaming console, and a gaming session. Participants danced to the song "Love Me Again" on a Just Dance 2015 program on Xbox 360 Kinect, Wii-U, PS3 Move, and a control YouTube. EE and HRR were calculated using FT4 Polar Heart Rate Monitor. One-way repeated measures ANOVA indicated no significant differences in energy expenditure across the consoles, F(2.74, 65.86)=0.65, p=.570. The paired samples t-test indicated the HRavg for the Xbox 360 Kinect (117±18 bpm) was significantly greater than the HRavg for the Control (112±16 bpm), t(24)=3.03, p=.006. About a third (28%-36%) of participants met moderate levels of intensity while exergaming. Dancing on all three major gaming consoles and YouTube video increase energy expenditures and can be used as an alternative form of exercise with the ability to achieve moderate levels of intensity.